Power Spectral Analysis in Lateralized Temporal Lobe Epilepsy: An MEG Study. Issue 3 (February 2019) - Li, Yuejun; Wu, Ting; Jiang, Tianzi
Abstract: In clinic, temporal lobe epilepsy (TLE) patients with visually normal MRI findings are more difficult to definitively diagnose than MRI-positive TLE patients. Spectral power can reflect the frequency characteristics of brain activity. In order to find biomarkers for discriminating MRI-negative TLE patients from healthy controls, magnetoencephalograms were recorded for 20 left and 23 right TLE patients with normal MRI results and 22 healthy controls in a no-task, eyes-closed condition. The regional and global powers of the patients and controls in the main frequency bands were analysed. Compared with the healthy controls, the left TLE group presented significantly increased powers in the left temporal region, whereas the right TLE group exhibited significantly increased powers in the right temporal region in the delta and theta bands. In the global power, the right TLE group showed significant increases in the delta and theta bands when compared with the healthy controls. Our results suggest that in the delta and theta bands, regional average powers in the left and right temporal regions can be taken as biomarkers for distinguishing MRI-negative TLE patients from healthy controls.